Determining the Efficiency of Field Machines System up and transport in the Ingenio Pantaleon using cyclic diagrams in the sugar harvest 2010/2011 - Rivera, Ricardo; Sánchez Murillo, Norwin Bianell; Ríos Carrasco, Gerardo (Nexo Revista Científica, 2012)
The agricultural engineering, related to the mechanized processes, is not limited to estimate the machines performance in a fixed state of the system. Indeed, it tries to predict the exact state of the system at any time with the purpose of identifying the activities of the machine system, and find the field efficiencies of the system, and labor efficiency. Furthermore, conduct an analysis of the cycle times in real-time. This study helped to find in practice, at a pilot level, the field efficiencies; labor efficiency, and the machines performance. Moreover, we identified the factors that restrict the machine system in the process of rise and transport of sugar cane harvest of Ingenio Pantaleón in El Viejo, Chinandega, Nicaragua DOI: http://dx.doi.org/10.5377/nexo.v25i2.676